EXPANSION STRATEGY OF THE SHADDAY RESTAURANT TO GENERATE NEW POSITIONING IN BAHIA DE CARAQUEZ - Galdea, Bryan Bolívar Gonzabay; Zambrano, Lilia Moncerrate Villacis (Seven Editora, 2024)
The research aimed to expand its presence in the gastronomic market in Bahía de Caráquez, managing to emphasize the importance of using effective marketing strategies to stand out and attract customers, as well as the importance of maintaining the quality of food and service during expansion. The methodology used was quantitative and qualitative, based on descriptive research. The technique used in the survey process, the data collected were tabulated through the spss25 software. The research had a preponderant element, highlighting that Bahía de Caráquez is a growing tourist destination. Therefore, the expansion of Shadday restaurant is of vital importance at this time, taking advantage of the need and the opportunity to offer an attractive gastronomic proposal for tourists and for the economic development of the place by providing. to local and national-international tourists a full satisfaction in the tourist journey undertaken. DOI:https://doi.org/10.56238/sevened2024.037-037